Stenosing tenosynovitis with rice bodies formation diagnosed by ultrasound: A case report. Issue 7 (18th February 2022) - Ge, Lei; Zhang, Lei; Lu, Libin
Abstract: Rationale: Rice bodies are usually found in several nonspecific chronic inflammatory diseases that are symptomatically dominated by primary disease and local compression symptoms. Rice bodies are usually detected by magnetic resonance imaging; however, some remote areas and areas with poor economic conditions do not have access to magnetic resonance imaging examination, which leads to delayed diagnosis of the disease. Patient concerns: We report the case of a 62-year-old man with pain in the metacarpophalangeal joint of his right middle finger and limited flexion activity of his middle finger. Diagnoses: The mass was 1 cm, well-circumscribed, soft, and painless. Ultrasound showed stenosing tenosynovitis with rice body formation. Interventions: The patient underwent tenosynovectomy with synovectomy of the right middle finger tendon sheath under plexus block anesthesia. Outcomes: No postoperative complications were noted. A 6-month follow-up showed no recurrence. The activity of the patient's middle finger improved significantly. Lessons: Stenosing tenosynovitis with rice body formation is a very rare condition, and we use ultrasound for diagnosis. Ultrasound is convenient, rapid, inexpensive, and can obtain blood flow information, facilitate disease follow-up, and even allow ultrasound localization in advance for guided needle biopsy.